Polityka językowa Szwecji - Iwona Kowal, Iwona Kowal (Scripta Neophilologica Posnaniensia, 2020)
The paper presents language policy in Sweden from 16th to 21st century. During many centuries Sweden aimed at making Swedish the dominant language in every domain and for every national group living in Sweden. Currently, Swedish has been recognized as the main language in Sweden which implicates the use of other languages in the country. Many activities are carried out in order to make the language used in public institutions easy and intelligible. Sweden offers courses in Swedish for immigrant children and adults, as well as courses in minority languages spoken as first languages and in sign language. There are also many institutions in Sweden which act in order to cultivate and promote Swedish.